Dupuytren’s disease and collagenase: evidence for a paradigm shift in management - Jessica A Paynter; Vicky Tobin; Warren M Rozen; David J Hunter-Smith (Australasian Journal of Plastic Surgery)
**Introduction**: Dupuytren’s disease is a common condition that leads to significant functional impairment of the hand. The recent introduction of collagenase clostridium histolyticum as a therapeutic option has changed the approach to disease management. Currently no non-surgical management paradigm exists for treating Dupuytren’s disease within Australia.